Effects of various analgesics on pain perception and rate of tooth movement: a randomized controlled clinical study - Abdaljawwad, Asem A; Al-Groosh, Dheaa H (Journal of Baghdad College of Dentistry, 2022)
Background: Pain is one of the most reported side effects of orthodontic treatment despite the advanced technology in orthodontics. Many analgesics have been introduced to control orthodontic pain including acetaminophen and selective and nonselective nonsteroidal anti-inflammatory drugs. The great concern about these drugs is their adverse effect on rate of teeth movement. Aims: The purpose of this study was to evaluate and compare the effect of acetaminophen, ibuprofen and etoricoxib on pain perception and their influence on the rate of teeth movement during leveling and alignment stage. Methods: Forty patients were evenly and randomly distributed in a blinded way to one of four groups: placebo (starch capsules), acetaminophen 500mg thrice daily, ibuprofen 400mg thrice daily, and etoricoxib 60mg once daily. The drugs were given one hour before bonding and archwire placement and continued for three days. A visual analogue scale was used to express pain levels before and after archwire placement, on the first, second, third, and seventh day. Little’s irregularity index was measured before bonding and at every activation visit until the end of the alignment and leveling stage. Results: All three drugs showed a lower pain level than placebo at the bonding and first activation visits. Etoricoxib showed the least pain level among other drugs followed by ibuprofen. No statistically significant differences were found between the drug groups and the placebo at the second and third activation visits. No statistically significant differences were detected between the 4 experimental groups concerning the rate of teeth movement. Conclusions: The three drugs were only effective in controlling pain during the first two visits of orthodontic treatment; and etoricoxib 60mg/day was the best. All three drugs had no influence on rate of teeth movement when used in their least recommended dose.